ELIMINASI POTENSI MUDA PADA KEGIATAN SUPPLY SMALL PART DI LOGISTIC SUPPLY PARTNER (LSP) MACHINING PT. ASTRA DAIHATSU MOTOR – ENGINE PLANT - Talsania Pratiwi; Agustian Suseno (JURNAL REKAYASA SISTEM INDUSTRI, 2021)
Astra Daihatsu Motor Engine Plant is a manufacturing company that produces motor vehicle engines. In the production process, Logistic supply partner Machining is a Logistics Sub-division whose task is to carry out the distribution process of small parts. Supply is carried out by Man power to the available shelves on the production line, in the process this activity has some potential for waste or what is called Muda. If supply activities experience problems that cause delays in the supply process, then the worst possibility is that the production line can stop and make the company suffer losses. For this reason, it is necessary to make efforts to eliminate these Muda potentials which is the purpose of this research. Process small part is carried out using dolly. This can lead to the potential for Muda. Of the 8 types of Muda, there are potential for 3 types, namely muda waiting, muda transportation and muda motion. For this reason, it is necessary to increase the number of dolly, in order to avoid the potential of double handling. In addition to this dolly, the manufacturing process must follow the rules of anthropometry, which is a collection of numerical data related to the characteristics of the human body in the form of size, shape and strength, as well as the application of these data to handling design problems. In addition to anthropometric data, data are also needed that will affect the design of the dolly such as the size and shape of the box to be carried. By using the 50% percentile of anthropometric data and also box size data, the dolly design to be made is 156 cm long, dolly width 83 cm, dolly height 83 cm and dolly handle height is 96 cm.